Novel Alternatively Spliced Endoplasmic Reticulum Retention Signal in the Cytoplasmic Loop of Proteolipid Protein-1 - Southwood, Cherie (J Neurosci Res, 2007)
Increased awareness about the importance of protein folding and trafficking to the etiology of gain-of-function diseases has driven extensive efforts to understand the cell and molecular biology underlying the life cycle of normal secretory pathway proteins and the detrimental effects of abnormal proteins. In this regard, the quality-control machinery in the endoplasmic reticulum (ER) has emerged as a major mechanism by which cells ensure that secreted and transmembrane proteins either adopt stable secondary, tertiary, and quaternary structures or are retained in the ER and degraded. Here we examine cellular and molecular aspects of ER retention in transfected fibroblasts expressing missense mutations in the Proteolipid Protein-1 (PLP1) gene that cause mild or severe forms of neurodegenerative disease in humans. Mild mutations cause protein retention in the ER that is partially dependent on the presence of a cytoplasmically exposed heptapeptide, KGRGSRG. In contrast, retention associated with severe mutations occurs independently of this peptide. Accordingly, the function of this novel heptapeptide has a significant impact on pathogenesis and provides new insight into the functions of the two splice isoforms encoded by the PLP1 gene, PLP1 and DM-20.